Litostratigrafi dan sedimentasi Formasi Kebo dan Formasi Butak di Pegunungan Baturagung, Jawa Tengah Bagian Selatan - Surono Surono (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no4.20081Lithologically, the Nampurejo Pillow Lava, Kebo and Butak Formations, which are dominated by volcanic rocks, spread west - eastly, along the northern foot of the Baturagung Mountains. The Nampurejo Pillow Lava, which has an Early Oligocene age, is overlain by the Late Oligocene - Early Miocene Kebo and Butak Formations successively. The Nampurejo Pillow Lava consists of basaltic pillow-lavas showing pillow structures and they are intercalated by black sandstones. The Kebo Formation comprises alternating sandstone and pebbly sandstone with intercalations of siltstone, claystone, tuff, and shale. On the other hand, the Butak For- mation is composed of polymic breccia with intercalations of sandstone, pebbly sandstone, claystone, and siltstone/shale. The three units were deposited in a deep – shallow marine basin, which was filled by volcanic prod- ucts. Compared to the lower part of the Kebo Formation, volcanic activities during the deposition of the upper part of the Kebo Formation and the Butak Formation were more active.